Implementasi Hubungan Media pada Divisi Komunikasi & CSR PT PTP - Nada Adilah Apriana (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aimed to determine the media relation activities of the Corporate Communication and CSR Division of PT PTP (a government owned enterprise). This study used a qualitative method with a descriptive approach. The informants were 3 staffs from Communication and Corporate Department, Corporate Communication and CSR Staff. The researchers used interview, observation and documentation analysis techniques to gain the data. The result of the research showed that media relation activities conducted by sharing to the media about formal informations, events, or daily activities of the enterprise. However, the media relation by means of pers conference, announcement, e-buletin, and writing media release to the mass media. Keywords: media relations, media release, qualitative descriptive research.